Revision of the genus Caenota Mosely (Trichoptera: Calocidae), with descriptions of 2 new species and the larva of C. nemorosa Neboiss - Shackleton, M.e.; Webb, J.m. (Zootaxa, 2015)
The caddisfly genus Caenota Mosely 1953 (in Mosely & Kimmins 1953) currently contains 5 species known from eastern Australia. Caenota is distinguished from other Calocidae genera by having adult males with greatly expanded maxillary palpi and a large membranous process associated with the antennal scape. Of the 5 described species, the larvae of only 1 is known. Here, we describe 2 new species, Caenota cudonis sp. nov. and C. equustagna sp. nov., from adult, larval, and pupal material. Also, we describe for the first time the larva of C. nemorosa Neboiss. These descriptions increase the number of Caenota species to 7 and the number of associated and described larvae to 4. This paper also provides descriptions of features associated with the adult head capsule of all described species of Caenota. Each of the known species is considered, with illustrations and re-descriptions of these features given.